MITATT mode in DDR heterostructure Impatt - Khan R.U.; Chakrabarti P.; Pal B.B. (My University, 2025)
Large signal characterisation of double heterostructure DDR Impatt diode has been carried out in the millimeter-wave range considering the MITATT mode of operation. The structure of the device is p+-p2-p1-n1-n2-n+ where impact ionisation and tunneling takes place in the p1-n1 region. In this study we have considered two well-known heterostructures, e.g., InP/GaInAs/InP and InP/InGaAsP/InP and one nonconventional structure GaAs/InP/GaAs. The theoretical results of the performances of these devices as regards of output power, efficiency, and negative conductance revealed that the structures are quite promising as the source of power in the millimeter-wave range. The analysis may be used for other mm wave DDR heterostructure Impatts. © 1987 Springer-Verlag.